If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -9) = 16x Reorder the terms: 4(-9 + x) = 16x (-9 * 4 + x * 4) = 16x (-36 + 4x) = 16x Solving -36 + 4x = 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. -36 + 4x + -16x = 16x + -16x Combine like terms: 4x + -16x = -12x -36 + -12x = 16x + -16x Combine like terms: 16x + -16x = 0 -36 + -12x = 0 Add '36' to each side of the equation. -36 + 36 + -12x = 0 + 36 Combine like terms: -36 + 36 = 0 0 + -12x = 0 + 36 -12x = 0 + 36 Combine like terms: 0 + 36 = 36 -12x = 36 Divide each side by '-12'. x = -3 Simplifying x = -3
| 0.5=0.5i-2 | | 12+3x+13=14 | | -5.1+a=-6.6 | | 28=y+14 | | 26x+14=5(5x+5) | | w-83=-100 | | 0=19+t | | 2X+1=3X-11 | | 7+2X+1=3X-11 | | y+80=-45 | | n-24=-16 | | -54+m=82 | | 30x^2-44x+16=0 | | y+8=21 | | a-9=13 | | 4x-3(x-2)=16 | | 250+14h=22h | | 3=5x+12 | | t+(2t+4)=-5 | | 8x/3-5x/4=-13 | | 5/25=y/85 | | -(5b+5)-5=1-(5b-1) | | -36=4w | | 11=3-7x | | X^3-2X+0.5=0 | | X^3-2X-0.5=0 | | 22=2c | | -2(2(2)-4)=-4(-2+2) | | 4x^2+9x-2=0 | | .90x+.52(2-x)=.10(-118) | | 3x-16cm=200cm | | 7x+2[3(1-x)]=14 |